The Puerto Rican Flag - A Study in Vexillology - Carlos A. Morales-Ramirez (Research in Social Sciences and Technology- OpenED Network, 2018)
This study tests Puerto Ricans' knowledge about the national and municipal flag, since it is known that teaching with flags is part of the social studies standards of the island. Two questionnaires were provided to 50 participants to test their knowledge of the national, municipal and Latin American flags. For the national and municipal flags, the participants were asked to provide the symbolism. A total of 96% drew the national flag correctly, although no one identified all the symbolisms correctly. Only 2% of the participants identified all Latin American flags correctly. A Chi-square test was performed to test if flag knowledge and level of education were independent variables. The test value was 0.30 which is greater than the P > 0.10; therefore, the null hypothesis was accepted: Ho = the level of schooling of the participants and their knowledge of the Puerto Rican flag are independent.